3D MODELLING OF STRUCTURAL ANISOTROPY OF THE ROCKS - PAVLOV, G.; INDUTNYI, F.; INDUTNYI, A.; FILIPOV, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The peculiarities of the capture and digital analysis of structures of the rocks in geology are discussed in this article. Comparison by precision of parallel slicing with other widely used methods like X-RAY tomography and µCT is mentioned here. Achievements in these industries allow getting high-quality rasters and triangulated (real-time) models of structures of granites. Moreover, self-developed mathematical algorithm is applied to the problem of measurement of anisotropy of environment. By using such algorithm it becomes possible to collect statistical information from the analysis of 3d-image of structure.